Age related changes in the vas deferens of Gaddi goat (Capra hircus) - An anatomical study - ARCHANA, ARCHANA; KATIYAR, R S; SHARMA, D N; FAROOQUI, M M (The Indian Journal of Animal Sciences, 2011)
The gross anatomy and histology of vas deferens were investigated in 30 male Gaddi goats (one day-old to 73 months old), divided into 3 groups, viz. prepubertal (one day-old to 18 months to60 months) animals- with 10 animals in each group. The vas deferens extended from cauda epididymis to pelvic urethra and had extra-abdominal, abdominal and ampullary parts. It dilated near its termination to yield ampullary part. The ampulla contained tubulo-alveolar glands in the mucosa, which were few in new born kids and more widely spread in the pubertal and post-pubertal animal. The length of various components did not differ significantly on either side but the ampulla was always longer on left side. At birth the lining epithelium was simple columnar, which transformed to pseudostratified ciliated columnar type in pubertal animals. The epithelial cells appeared more vacuolated in pubertal and post-pubertal animals.